Implementasi Hukum Pemungutan Suara Ulang di TPS 04 Selat Utara pada Pilkada Serentak 2024 Kabupaten Kapuas - Wahipal Akhmad; Dadin Eka Saputra; M. Rosyid Ridho (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the implementation of the PSU regulation in handling violations during the Regional Head Election (Pilkada) at Polling Station 04, Selat Utara Village, Kapuas Regency, and to identify the factors that hinder its implementation. This research employed an empirical legal research method with a qualitative approach. Primary data were collected through interviews with the General Election Commission (KPU) of Kapuas Regency, the Election Supervisory Agency (Bawaslu) of Kapuas Regency, and the Integrated Law Enforcement Center (Sentra Gakkumdu). Secondary data were obtained through a literature review of statutory regulations, official documents, and relevant academic literature. The data were analyzed qualitatively using Lawrence M. Friedman's legal system theory, which consists of legal substance, legal structure, and legal culture. The findings reveal that the implementation of the PSU regulation was carried out in accordance with the prevailing legal provisions through coordinated actions among the KPU, Bawaslu, and Sentra Gakkumdu, thereby restoring the procedural legality of the voting process. Nevertheless, several challenges remain, including the limited capacity of election officials, time constraints in organizing the re-voting process, technical coordination among institutions, and a legal culture that has not yet fully supported professional, accountable, and integrity-based electoral administration.